Genetic Diversity and Connectivity in Maurolicus muelleri in the Bay of Biscay Inferred from Thousands of SNP Markers - Rodriguez-Ezpeleta, Naiara; Álvarez, Paula; Irigoien, Xabier (Frontiers in Genetics, 2017)
Mesopelagic fish are largely abundant poorly studied fish that are still intact, but which, due to their potentially great added value, will be imminently exploited by humans. Therefore, studies that provide information to anticipate the anthropogenic impact on this important resource are urgently needed. In particular, knowledge about their connectivity, potential adaptation and resilience are needed. This information can be obtained through the analysis of genome-wide markers which are now relatively easily and cost-efficiently discovered thanks to high-throughput sequencing technologies. Here, we have generated thousands of SNP markers in Maurolicus muelleri, based on the restriction-site associated DNA sequencing method, and preformed population connectivity and genetic diversity analyses in a subset of samples collected from the Bay of Biscay. Our study proves the method valid for obtaining genome-wide markers in this species and provides the first insights into the population genomics of M muelleri. Importantly, the genomic resources developed here are made available for future studies and set the basics for additional endeavors on this issue.